Comparison Between Peer-Led and Teacher-Led Education in Tuberculosis Prevention in Rural Middle Schools in Chongqing, China. (March 2015) - Liu, Qin; Liu, Liping; Vu, Huyen; Liu, Xiaoxue; Tang, Shenglan; Wang, Hong
The aim of this study was to investigate the efficacy of tuberculosis (TB) education through a comparison of peer-led and teacher-led methods of education about TB prevention among middle school students in rural Chongqing, China. A preintervention and postintervention questionnaire survey was conducted in 2 different middle school student groups to measure changes in knowledge, attitude, and practice (KAP) status of those students before and after each TB education program. Of 1265 students participating in the preintervention survey, 1176 completed the postintervention survey. KAP scores of both peer-led and teacher-led groups after intervention improved by as much as 2 times compared with before the intervention and those of the control group ( P < .01). KAP scores of immediate evaluation were higher than those of long-term evaluation in the teacher-led education group ( P < .01). The teacher-led group had a larger improvement than the peer-led group in practice scores ( P < .01) in immediate effect evaluation.